Benthic periphyton from Pennsylvania, USA is a source for both hepatotoxins (microcystins/nodularin) and neurotoxins (anatoxin-a/homoanatoxin-a). (August 2018) - Foss, Amanda J.; Butt, Jeffery; Aubel, Mark T.
Abstract: In 2016, the Pennsylvania Department of Environmental Protection conducted a limited survey of streams in the Susquehanna River basin in Pennsylvania, USA, to screen for microcystins/nodularins, anatoxin-a (ATX) and homoanatoxin-a (HTX). Testing revealed the presence of HTX in samples collected from the Pine Creek basin, with ATX present at lower levels. Microcystins/nodularins (MCs/NODs) were also tested and found to be concomitant, with NOD-R confirmed present by LC-MS/MS. Highlights: Periphyton samples were collected from Pennsylvania, USA in 2016. ELISA, Individual Variant Analysis (LC-MS/MS) & MMPB were used to measure Microcystins/Nodularins. LC-MS/MS was used to characterize anatoxin analogs. Anatoxin-a, Homoanatoxin-a were confirmed present in some samples. Dihydrohomoanatoxin-a and Epoxyanatoxin-a were also tentatively identified.